China’s Engagement with the Islamic Nations
X, 249 p. 10 illus., 6 illus. in color.
Keywords: This book provides a critical insight into China's evolving socio-cultural relations with Islamic countries in the face of growing geopolitical uncertainty. It considers both the historical and socioeconomic aspects of China-Islamic countries relations to present a balanced analysis of the effectiveness of the Belt and Road Initiative (BRI) plan and the current and future evolution of cooperation. The book also sheds new light of the impact on individual economic sectors, considering both the micro- and macro-effects on various stakeholders as the global community navigates an increasingly precarious power struggle between dominant world powers. The book presents contributions from a variety of fields to provide a multi-faceted breakdown of the challenges that remain for the myriad of relationships in the years to come. .